Role of the western tropical Pacific in the North Pacific regime shift in the winter of 1998/1999. Issue 9 (17th September 2014) - Jo, Hyun‐Su; Yeh, Sang‐Wook; Kirtman, Ben P.
Abstract In this study, we examine the role of the western tropical Pacific in the North Pacific regime shift during the winter (December–January–February) of 1998/1999. The North Pacific regime shift in the winter of 1998/1999 is characterized by a dipole‐like structure along 40°N where significant warming is prominent in the western and central North Pacific. This shift might have been associated with an abrupt warming in the western tropical Pacific after 1998/1999, in the North Equatorial Current (NEC) bifurcation region (8°N–18°N, 125°E–160°E) in particular. The NEC bifurcation region experiences a regime shift from cooling to warming during the 1998/1999. Consequently, the Kuroshio current, which originates in the NEC bifurcation region, could transport the anomalous warm water into the North Pacific. In addition, a sudden shift in the NEC bifurcation latitude to the south also contributes to the 1998/1999 regime shift in the North Pacific. We suggest a possible mechanism that could have caused the regime shift in the NEC bifurcation region during the 1998/1999. An abrupt deepening of the thermocline depth in the NEC bifurcation region from 1997/1998 to 1998/1999, which is associated with the biggest El Niño in 1997/1998 and a subsequent La Niña event in 1998/1999, plays a role in initiating the shift in the NEC bifurcation region. Subsequently, the frequent occurrence of the La Niña events after 1998/1999 plays a role in maintaining the regime shift toward warming by sustaining a deepening of the thermocline depth.